Professionalisation of family farming – Tools for technical and organisational capacity-building of farmers’ organisations in sub-Saharan Africa - Etobe, J.M. (CTA / ISF, 2015)
In order for farmers to be recognised as stakeholders in their own right and for them to meet the high expectation of feeding the world by producing more and better and with less means, we must form strong, representative and professional farmers’ organisations. This guide should contribute to the creation of proper farmers’ organisations.